2022
DOI: 10.1007/s00415-022-11230-8
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in motor symptoms, physical fatigue, and self-rated change perception in functional motor disorders: a prospective cohort study of a 12-week telemedicine program

Abstract: Background Functional motor disorders (FMDs) are highly disabling conditions associated with long-term disability, poor quality of life, and economic burden on health and social care. While multidisciplinary 5-days rehabilitation programs have been shown to reduce motor and non-motor symptoms, long-term management and monitoring in FMDs remain an unmet need. Aim To compare a 12-weeks telemedicine program against a 12-weeks self-management program after a 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 56 publications
(111 reference statements)
0
4
0
Order By: Relevance
“…Patients with functional movement disorders (n=64) who received home-based physical exercises from a physiotherapist did not show improvements in the Brief Pain Inventory compared with those in the self-management group. 35 A randomised feasibility study of physiotherapy for patients with functional motor disorders (n=57) found no significant changes in SF-36 bodily pain, despite improvements in physical and social function. 29 Likewise, a pilot study of tailored psychotherapy for 63 patients with functional neurological symptoms identified global improvements in the SF-36 but not in bodily pain.…”
Section: Pain Treatment Approaches In Fndmentioning
confidence: 99%
“…Patients with functional movement disorders (n=64) who received home-based physical exercises from a physiotherapist did not show improvements in the Brief Pain Inventory compared with those in the self-management group. 35 A randomised feasibility study of physiotherapy for patients with functional motor disorders (n=57) found no significant changes in SF-36 bodily pain, despite improvements in physical and social function. 29 Likewise, a pilot study of tailored psychotherapy for 63 patients with functional neurological symptoms identified global improvements in the SF-36 but not in bodily pain.…”
Section: Pain Treatment Approaches In Fndmentioning
confidence: 99%
“…Further research should also elucidate if the perception of persistent PCS patients of themselves and their illness would be a factor in influencing or evaluating the physiological and psychological outcomes following holistic treatment, as it was suggested that selfperception and expectations related to the disease could at least partly change the treatment and recovery outcomes in FNDs and other chronic neurological disorders [96][97][98].…”
Section: Critiques and Limitations Of The Fnd Model For Ppcsmentioning
confidence: 99%
“…FMDs are involuntary but learnt altered movement patterns caused by abnormal self‐directed attention and movement prediction, resulting in a movement generated without a normal sense of agency 1,3,17–19 . Within this perspective, multidisciplinary intensive rehabilitation, supported by telemedicine, is a widely recognized strategy for the PwFMD management 20–23 . Retraining movement through diverted attention and changing maladaptive symptoms‐related behaviors can reduce disability and improve patients’ quality of life 20–23 .…”
mentioning
confidence: 99%
“… 1 , 3 , 17 , 18 , 19 Within this perspective, multidisciplinary intensive rehabilitation, supported by telemedicine, is a widely recognized strategy for the PwFMD management. 20 , 21 , 22 , 23 Retraining movement through diverted attention and changing maladaptive symptoms‐related behaviors can reduce disability and improve patients’ quality of life. 20 , 21 , 22 , 23 Future research directions require developing interventions for treating specific functional symptoms based on the pathophysiological features of FMDs, such as the altered focus of attention, sense of agency, and belief/expectations.…”
mentioning
confidence: 99%
See 1 more Smart Citation